SNHG 6 promotes the progression of Colon and Rectal adenocarcinoma via miR-101-3p and Wnt/β-catenin signaling pathway - Shao, Qianwen (BMC Gastroenterol, 2019)
BACKGROUND: Small nucleolar RNA host gene 6 (SNHG6) regulates diverse biological processes in cancers. Potential function of SNHG6 in human colon and rectal adenocarcinoma (CRC) was evaluated. METHODS: Quantitative real-time polymerase chain reaction, MTT assays, Colony formation assays, Transwell assay, Western Blotting and Luciferase reporter assays were performed to measure the biological functions and potential molecular mechanisms of SNHG6 in CRC. RESULTS: SNHG6 was over-expressed in CRC, and high expression of s SNHG6 were associated with short survival times. We then identified miR-101-3p as an inhibitory target of SNHG6. Knockdown of SNHG6 significantly decreased miR-101-3p expression. Moreover, silenced SNHG6 obviously inhibited CRC cell growth, weakened cell invasion capacity and blocked the Wnt/β-catenin signaling pathway. CONCLUSION: SNHG6 could regulate the progression of CRC via modulating the expression levels of miR-101-3p and the activity of Wnt/β-catenin signaling.